Perbandingan Life Skills Menggunakan Model Talking Chips, Class Wide Peer Tutoring, Group Resume - Sylvia Imara Nurlaela; Edy Purnomo; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2017)
The purpose of this research was to know the difference of life skills use of cooperative learning model of Talking Chips, Class Wide Peer Tutoring and Group Resume. The method used quasi experiment with comparative approach. The study design used post test only. The population this research was VII grade in SMP Negeri 1 Pesawaran and those sample from 3 classes using random Cluster Random Sampling. Data collection technique used observation. Hypothesis testing used one-way analysis of variance and countinu test t-Dunnet. Based on analysis of result data: 1. There is a difference life skills learning model Talking Chips, Class Wide Peer Tutoring and Group Resume, 2. Life skills learning model Talking Chips better than Class Wide Peer Tutoring, 3.Life skills Talking Chips learning model better than Group Resume and, 4.Life skills Class Wide Peer Tutoring learning model better than Group Resume.Tujuan penelitian ini untuk mengetahui perbedaan life skills penggunaan model pembelajaran kooperatif tipe Talking Chips, Class Wide Peer Tutoring dan Group Resume. Metode yang digunakan adalah eksperimen semu dengan pendekatan komparatif. Desain penelitian yang digunakan Only One Posttest. Populasi penelitian ini siswa kelas VII SMP Negeri 1 Pesawaran dan sampel sebanyak 3 kelas menggunakan Cluster Random Sampling. Teknik pengumpulan data melalui lembar observasi. Pengujian hipotesis menggunakan analisis varians satu jalan dan uji lanjut t-Dunnet. Berdasarkan analisis data diperoleh hasil: 1. Ada perbedaan life skills antara model pembelajaran Talking Chips, Class Wide Peer Tutoring dan Group Resume, 2. Life Skills yang model pembelajaran Talking Chips lebih baik dibandingkan Class Wide Peer Tutoring, 3. Life skills yang model pembelajaran Talking Chips lebih baik dibandingkan Group Resume dan, 4. Life skills yang model pembelajaran Class Wide Peer Tutoring lebih baik dibandingkan Group Resume.Kata kunci: life skills, talking chips, class wide peer tutoring, group resume